Women, gender and transnational lives : Italian workers of the world - Gabaccia, Donna R., 1949-; Iacovetta, Franca, 1957- (Studies in gender and history., 2002)
In this transnational analysis of women and gender in Italy's world-wide migration, Franca Iacovetta and Donna Gabaccia challenge the stereotype of the Italian immigrant woman as silent and submissive; a woman who stays 'in the shadows.'